Digital Transformation through Mining and DevOps Learning: A Study in the Context of Cyber-Physical Systems - Barros, Daniel D’Angelo Resende; Horita, Flávio (Companion Proceedings of the Brazilian Symposium on Information Systems (SBSI), 2020)
Digital Transformation is a process that aims at creating more value for customers through digital tools. DevOps results in the collaboration among Development (Dev), and Operations (Ops) teams, and this alignment can make a Digital Transformation happen, encouraged by the Information Technology area. Thus, the goal of this project is creating a Digital Transformation framework through DevOps. This framework will run in cycles and , from data collected from DevOps process, will use Data Mining and Machine Learning to get relevant information, improving the Digital Transformation proposed. This framework will be validated in a cyber physical system, using continuous delivery, allowing the control of physical entities (humanoids robots).